Dynamic crystal rotation resolved by high‐speed synchrotron X‐ray Laue diffraction. (1st April 2016) - Huang, J. W.; E, J. C.; Huang, J. Y.; Sun, T.; Fezzaa, K.; Luo, S. N.
Abstract : High‐speed (submicrosecond) translation and rotation of crystals are tracked in real time via simultaneous synchrotron X‐ray imaging and Laue diffraction. Abstract : Dynamic compression experiments are performed on single‐crystal Si under split Hopkinson pressure bar loading, together with simultaneous high‐speed (250–350 ns resolution) synchrotron X‐ray Laue diffraction and phase‐contrast imaging. A methodology is presented which determines crystal rotation parameters, i.e. instantaneous rotation axes and angles, from two unindexed Laue diffraction spots. Two‐dimensional translation is obtained from dynamic imaging by a single camera. High‐speed motion of crystals, including translation and rotation, can be tracked in real time via simultaneous imaging and diffraction.